2011
DOI: 10.1038/onc.2011.137
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin and its analogs inhibit cancer cell glycolysis by targeting tumor pyruvate kinase-M2

Abstract: We recently reported that shikonin and its analogs were a class of necroptotic inducers that could bypass cancer drug resistance. However, the molecular targets of shikonin are not known. Here, we showed that shikonin and its analogs are inhibitors of tumor-specific pyruvate kinase-M2 (PKM2), among which shikonin and its enantiomeric isomer alkannin were the most potent and showed promising selectivity, that is, shikonin and alkannin at concentrations that resulted in over 50% inhibition of PKM2 activity did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
309
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(328 citation statements)
references
References 41 publications
10
309
2
7
Order By: Relevance
“…SKN, a potent PKM2 inhibitor, which has previously been reported to limit glycolysis in tumor cells and protect mice from sepsis through the inhibition of PKM2 in macrophages (18,30), was used in this study. Our in vitro and in vivo experiments demonstrate that SKN inhibits the Hcy-induced upregulation of PKM2 enzyme activity and metabolic reprogramming, leading to the prevention of Hcy-induced B cell proliferation and Ab secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SKN, a potent PKM2 inhibitor, which has previously been reported to limit glycolysis in tumor cells and protect mice from sepsis through the inhibition of PKM2 in macrophages (18,30), was used in this study. Our in vitro and in vivo experiments demonstrate that SKN inhibits the Hcy-induced upregulation of PKM2 enzyme activity and metabolic reprogramming, leading to the prevention of Hcy-induced B cell proliferation and Ab secretion.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the potential role of PKM2 in regulating Hcyinduced metabolic changes and B cell activation, the potent PKM2 inhibitor SKN was used. SKN can selectively inhibit the glycolytic enzyme activity of PKM2 without affecting other pyruvate isoforms and may limit the subsequent lactate production and oxidative metabolism in mitochondria (30). We first performed a dose titration of SKN to determine the optimal dose for our experiments.…”
Section: Pkm2 Mediates Hcy-induced B Cell Proliferation and Ab Secretmentioning
confidence: 99%
“…α-Methyl-n-butylshikonin (MBS), one of the shikonin derivatives, is a naphthoquinone pigment isolated from the traditional medical herbs Lithospermum erythrorhizon ( Figure 1A) (Chen et al, 2011). Previous studies have demonstrated that shikonin and its derivatives possess multiple biological functions such as anti-microbial, antiinflammatory, anti-HIV and anti-platelet effects (Tanaka et al, 1986;Ko et al, 1995;Shen et al, 2002;Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin (Sigma-Aldrich), um inibidor da PKM2, foi utilizado em experimentos in vitro e in vivo (CHEN et al, 2011). In vitro, shikonin foi adicionado às culturas de linfócitos T nas concentrações de 0.3, 1 e 3 µM.…”
Section: Ferramenta Farmacológicaunclassified
“…Shikonin foi descrito como um potente inibidor da PKM2 em células tumorais e macrófagos (CHEN et al, 2011;YANG et al, 2014b). Sabendo que os níveis de expressão de PKM2 e fosfo-PKM2 estão aumentados durante a diferenciação de linfócitos Th17, avaliou-se qual a consequência da inibição farmacológica de PKM2 sobre a geração destas células.…”
Section: Th17 In Vitrounclassified